Long-Term Empirical Studies Highlight Multiple Drivers of Temporal Change in Bird Fauna in the Wet Forests of Victoria, South-Eastern Australia - Lindenmayer, David; Bowd, Elle; McBurney, Lachlan (Frontiers in Ecology and Evolution, 2021)
Birds are high profile elements of the vertebrate biota in almost all terrestrial ecosystems worldwide. Many studies have uncovered evidence of a decline in bird biota, but temporal patterns of change vary among ecosystems and among bird species with different life history traits. Ecosystem-specific, long-term studies are critical to identify patterns of temporal change in bird fauna and the drivers of that change. Here we present a case study of patterns of change and the drivers of that change in the bird fauna of the Mountain Ash and Alpine Ash eucalypt forest ecosystems in south-eastern Australia. Using insights from observational studies and experiments conducted over the past two decades, we discuss the direct and interactive effects of fire and logging on birds. The extent and severity of wildfires have major negative effects on almost all bird species, and even more than a decade after the last major conflagration (in 2009), the vast majority of taxa are not recovering. Logging has markedly different effects on birds than those quantified for fire, and may have resulted in elevated levels of site occupancy in remaining uncut areas in the landscape. Both fire and logging have led to marked losses in the extent of old growth forest in Mountain Ash and Alpine Ash ecosystems. This is a concern given the strong association of most species of birds with old forest relative to younger age cohorts. Based on an understanding of the effects of fire and logging as drivers of change, we propose a series of inter-related management actions designed to enhance the conservation of avifauna in Mountain Ash and Alpine Ash ecosystems. A particular focus of management must be on the need to reduce the frequency and extent of wildfire and, in turn, significantly expand the extent of old growth forest, as this is where most bird species are most likely to occur and in the event of future wildfires, and where fire severity will be lowest. Expansion of the old growth estate will require commercial logging operations to be excluded from large parts of Mountain Ash and Alpine Ash forests.